Pendidikan Aqidah Tentang Qadha Dan Qadar: Strategi Menanamkan Pemahaman Takdir Kepada Generasi Muda Muslim - Hidayati, Yusranida; Fathimah, Laila; Karim, Pangulu Abdul (Journal Of Human And Education (JAHE), 2024)
Aqidah education plays a crucial role in shaping the character of a Muslim, particularly in understanding the concepts of qadha and qadar. Both are the sixth articles of faith that teach belief in Allah SWT's decree. However, modern challenges such as secularism and materialism hinder the instillation of this understanding. Therefore, relevant and effective educational strategies are needed to develop a profound understanding of qadha and qadar. This includes a holistic approach that involves the roles of parents, educators, and the social environment, as well as the integration of experiential learning methods. Through this approach, it is hoped that a comprehensive and applicable understanding of qadha and qadar can be realized in daily life. Keywords: Aqidah Education, Qadha, Qadar, Secularism, Materialism, Holistic Approach